Phyto-therapeutic Potential of Aconitum ferox Roots in CFA-induced Arthritis in Rat Model - Singhai, Ashish; Ahmad, Yusra; Patil, Umesh Kumar (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: To investigate the anti-arthritic potential of ethanolic extract of Aconitum ferox root (EAF) and isolation of a compound from the active fraction. Materials and Methods: The EAF obtained from successive solvent extraction was evaluated for antirheumatic action by complete Freund’s adjuvant (CFA) induced arthritis in adult Lewis rats (150-200gm) at 10mg/kg dose for prophylactic and therapeutic effect after acute toxicity study. Paw volume, body weight changes, locomotor activity, hemoglobin (Hb) count, erythrocyte sedimentation rate, LPO, and SOD levels were assessed in arthritic animals. These were supported by histological and radiological studies of the affected joints. Statistical analysis was performed using one way ANOVA followed by Dunnett’s test. p<0.05 was considered statistically significant. A compound isolated was characterized by spectroscopic and chromatographic techniques. Results: The EAF 10mg/kg showed a significant reduction in paw volume (58.32%), body weight, ESR (8.1-7.5 mm/h), and LPO level (37.5nmol/g). There was a significant increase in hemoglobin count (13.42g/dl), locomotors activity (92.95%), and SOD level (201U/mg). The isolated compound after TLC, UV, FTIR, and LCMS analysis was identified as delphinine. Conclusion: The data shows that EAF has anti-arthritic activity at 10mg/kg, p.o., and a compound delphinine isolated from it.
Keywords: Aconite; Anti-arthritic; Delphinine; Alkaloid; Vatsanabh; CFA